Die Entwicklung der HSH Nordbank als Landesbank - einige Einschätzungen - Norbert Dieckmann (Wirtschaftsdienst, 2013)
Die HSH Nordbank ist nach dem Beginn der internationalen Finanzkrise in wirtschaftliche Schwierigkeiten geraten. Sind ihre Probleme symptomatisch für die Lage der Landesbanken oder hatten Auflagen der EU-Kommission im Rahmen eines Beihilfeverfahrens die Schieflage verursacht? Die Mehrheitseigentümer der HSH Nordbank, Hamburg und Schleswig-Holstein, wurden bisher noch nicht stark liquiditätswirksam belastet. Das kann sich in Zukunft aber ändern. – – Some of the German 'Landesbanken' engaged in highly risky business with the acceptance of local politicians and then demanded bailouts during the financial crisis. The HSH Nordbank, the world's largest provider of ship financing, based in northern Germany, lost almost 2.8 billion euros in 2008. The two German shareholders, the states of Hamburg and Schleswig-Holstein, had to agree on a 13 billion euro bailout plan for the bank (3 billion euros in cash and a 'risk shield' of 10 billion euros). Furthermore, the German government provided the HSH Nordbank with 17 billion euros of liquidity guarantees under the Special Financial Market Stabilisation Fund (SOFFIN). In view of this situation, the following questions should be answered: What role did the merger of the Hamburger Landesbank and Landesbank Schleswig-Holstein play in the development of the HSH Nordbank? Was there a possibility to merge the HSH Nordbank with another bank to avoid the financial difficulties? Were the extensive conditions set by the EU Commission in the state aid proceedings too restrictive? What are the actual costs of the HSH Nordbank's bailout programme for the shareholders and their governmental budgets?
Keywords: G21; 330; Landesbank; EU-Beihilfenkontrolle; Schuldenübernahme; Staatshaftung; Schleswig-Holstein; Hamburg